Character Values and Fitness Elements in Bengkulu Traditional Games: Case Study Tutor Gala and ACO Traditional Games - Pebrisen, Iwin; Hanani, Endang Sri; Priyono, Bambang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to analyze the content of character values ​​and fitness elements in the traditional games Tutor Gala and Aco in the Kedurang community, South Bengkulu. The research was conducted using a qualitative case study type method. Data was collected using observation, interview, and documentation techniques and analyzed using an interactive model. The research results are that the traditional Tutor Gala and Aco games contain many values/characteristics, especially sportsmanship, honesty, discipline, cooperation, democracy, and hard work. Of these existing values, one of the most dominant values ​​is the value of collaboration. Next are the values ​​of sportsmanship, honesty, discipline, democracy, and hard work. The traditional games Tutor Gala and Aco are two traditional games that contain many fitness elements, namely endurance, speed, agility, and coordination. In conclusion, of the four fitness elements in the conventional games Tutor Gala and Aco, the most dominant aspects are speed, endurance, agility, and coordination. Keywords: Fitness, Traditional Games, Tutor Gala and Aco